Online Captive: The Impact of Social Media Addiction on Depression and Anxiety—An SEM Approach to the Mediating Role of Self-Esteem and the Moderating Effects of Age and Professional Status - Daniela-Elena Lițan (Behavioral Sciences)
In the “era” in which social networks have become an integral part of everyday life, this study aims to analyze the impact of social network addiction on mental health, with a focus on the manifestation of anxiety and depression symptoms. The relationship analyzed on a batch of a Romanian adult population, explained by self-esteem and influenced by factors such as age and professional status, highlights the fact that all age categories and professional status can be affected by addiction to the online environment but with different degrees of intensity. The analyses carried out using Structural Equation Modeling (SEM) suggest that young people and professionally inactive people are the categories with the highest degree of self-esteem impairment and with a high potential to manifest symptoms associated with depression and anxiety disorders, as a result of the intense use of social networks. The current study makes a significant contribution to the specialized literature, given the small volume of similar studies conducted on the adult population of Romania.